Case Study : Warung Kita / Nur Affina Iskandar Mustafa Kamal - Iskandar Mustafa Kamal, Nur Affina (2020)
Warung Kita has been established on 2014. This business has been operated around 6 years. It is located in Jalan Tanjung Tokong Lama, Georgetown, Penang. This business is run by Encik Mohd Syawal with his family members. This business focuses on selling variety traditional kind of food such as nasi lemak, ‘kuih-muih’ and other suitable dishes. It operates as early as 5.30 a.m. until 10.00 a.m. daily. Apart from that, they also provide ordering services for their customers that are interested to order in a mass amount